Necrotizing Encephalomyelopathy of Leigh: Neuropathological Findings in 8 Cases. Issue 239 (February 1970) - Dayan, A. D.; Ockenden, B. G.; Crome, L.
Abstract : Eight patients with necrotizing encephalomyelopathy are reported. Lesions were found only in the central nervous system. The principal sites affected were the caudate nuclei, putamina, periaqueductal tissues, tegmentum, and structures in the floor of the IVth ventricle. Lesions were also found in the centrum ovale, cerebellum, and the grey and white matter in the spinal cord. The histological findings were of spongy rarefaction, scarring, and excessive vascularity. The pattern of inheritance of necrotizing encephalomyelopathy suggests that it is due to an autosomal recessive gene. Though the disease closely resembles the encephalopathy of thiamine deficiency, morphological and biochemical evidence suggests that this is not a direct aetiological factor. It is possible that the condition is due to a disorder of lipoic acid metabolism, perhaps at a step near the thiamine-dependent stage of carbohydrate metabolism.